Being a mother with multiple sclerosis: Negotiating cultural ideals of mother and child. (May 2018) - Parton, Chloe; Ussher, Jane M; Natoli, Simone; Perz, Janette
Multiple sclerosis can impact affected women's experiences of motherhood through physical and cognitive impairment. This study examined how women construct and experience motherhood while living with multiple sclerosis. Twenty mothers diagnosed with multiple sclerosis took part in semi-structured interviews. Transcripts were analysed using theoretical thematic analysis, drawing on feminist poststructuralist theory to organise and interpret themes. Two main themes were identified: "Performing motherhood in the context of MS" and "Bringing up a 'good' child". "Performing motherhood in the context of MS" comprises the subthemes, "The self-sacrificing mother: Negating women's needs", "The unreliable mother: Adjusting day-to-day mothering practices", and "Resisting discourses of idealised motherhood". "Bringing up a 'good' child", comprises the subthemes, "The damaging mother: Fear of harming the child" and "The good mother: Caring and building resilience in the child". Women positioned themselves as failing to be good mothers, because of limitations to their mothering, and fear of damaging children. Focusing on building children's emotional resilience functioned to restore constructions of "good" mothering. Acknowledging how Western cultural ideals influence women's experience of mothering when living with chronic illness is important. Health professionals can provide support by addressing women's feelings of failure as mothers and supporting communication with children.